Construction and updating of a public events questionnaire for repeated measures longitudinal studies - Noone, Martha; Semkovska, Maria; Carton, Mary; Dunne, Ross; Horgan, John Paul; O'Kane, Breige; McLoughlin, Declan M. (Frontiers in Psychology, 2014)
Impairments of retrospective memory and cases of retrograde amnesia are often seen in clinical settings. A measure of the proportion of memories retained over a specified time can be useful in clinical situations and public events questionnaires may be valuable in this respect. However, consistency of retention of public events memory has rarely been studied in the same participants. In addition, when used in a research context, public events questionnaires require updating to ensure questions are of equivalent age with respect to when the test is taken. This paper describes an approach to constructing and updating a Public Events Questionnaire (PEQ) for use with a sample that is recruited and followed-up over a long time-period. Internal consistency, parallel-form reliability, test-retest reliability and secondary validity analyses were examined for three versions of the PEQ that were updated every six months. Versions 2 and 3 of the questionnaire were reliable across and within versions and for recall and recognition. Change over time was comparable across each version of the PEQ. These results show that PEQs can be regularly updated in a standardised fashion to allow use throughout studies with long recruitment periods.